Study of practice facilities and feasibility at the Private Vocational School with TKR competence in Bantul District - Agung Wibisono; Dianna Ratnawati (Jurnal Taman Vokasi, 2018)
This research aims to evaluate the level of the feasibility of practice facilities and infrastructure at five vocational high schools in Bantul District. This type of research is qualitative research with a case study method. This research took place at five vocational high schools in Bantul Regency namely SMK Ma'arif 1 Kretek Bantul, SMAK Putra Tama Bantul, SMK Muhammadiyah 1 Bantul, SMK Muhammadiyah Imogiri, and SMK Ma'arif Al-Munawwir Krapyak Bantul. Data collection techniques used in this study were observation, documentation, and interviews. The data analysis technique used is descriptive quantitative. The results of the study found that the level of feasibility of infrastructure for TKR practice at SMK in Bantul was feasible, with details as follows: SMK Ma'arif 1 Kretek Bantul is eligible (80%), SMK Putra Tama Bantul is very worthy (85%), SMK Muhammadiyah 1 Bantul is eligible (75%), SMK Muhammadiyah Imogiri is eligible (80%), and SMK Ma'arif Al-Munawwir Krapyak Bantul is eligible (65%). Furthermore, the feasibility level of TKR chassis practice facilities at five SMK in Bantul District is feasible, with details as follows: SMK Ma'arif 1 Kretek Bantul is eligible (65%), SMK Putra Tama Bantul is very worthy (80.7%), SMK Muhammadiyah 1 Bantul is very worthy (84.6%), SMK Muhammadiyah Imogiri is very worthy (84%), and SMK Ma'arif Al-Munawwir Krapyak Bantul is eligible (63.4%)